Competence approach in ecological education of engineering students - KOZLAKOVA, Galina; SAYENKO, Tatiana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The ways of modernization of ecological or environmental education inhigher technical school during the competency paradigm and in final phase ofthe Decade of Education for Sustainable Development (2011–2014) were discussed.